Peringkat Dan Penanganan Risiko Dominan Konstruksi Design And Build Jalan Tol Pada Pekerjaan Proyek Trans Sumatera Ruas Simpang Indralaya–Muara Enim Seksi Simpang Indralaya – Prabumulih - Auzan Nurtsani, Rifqi (Jurnal Etnik: Ekonomi-Teknik, 2023)
Prabumulih used thirty variables from the results of previous research which were then validated with experts and became a total of thirty-three variables. On these variables, interviews were conducted with respondents. The interview results were analyzed using spss and ranked based on the risk analysis. The results are then thrown back to the respondents for category risk mitigation (unacceptabrle). From these results, there are seven dominant risks. From these results, there are seven dominant risks. The dominant risk is divided into three categories, namely owner factors, implementing team factors and external factors that affect the Construction Design And Build of Toll Roads in Trans Sumatra Project Work Simpang Indralaya – Muara Enim Section Simpang Indralaya – Prabumulih Section